Alat Pengukur Ketinggian Air Berbasis Microcontroller Sebagai Peringatan Banjir Dengan Notification - Handayani, Indri; Setiadi, Ade; iman, Fajar nur (Pandawan Incorporation, Alphabet Incubator Universitas Raharja, 2019)
Ultrasonic sensor is a device that is often used in industrial companies. Ultrasonic sensor has a function as a detector and distance measuring. Ultrasonic sensor work is the sensor will emit ultrasonic waves on the surface and then catch it back, so the results obtained in accordance with the original state. Some car companies use this ultrasonic sensor on the car as a means to measure the distance so as not to collide with other vehicles. This sensor is very suitable for designing a water level gauge, because in addition to effective sensors also provide accurate results. From several experiments conducted, it was generated that ultrasonic sensors were quite effective in measuring at a distance of 1 cm - 300 cm. from the design of ultrasonic sensor-based water meter this results obtained will be displayed on the 16x2cm lcd screen as a giver of information and some led lights to provide restrictions of the height and buzzer as a warning sign that the maximum water level. Keywords: ultrasonic sensor, water level meter, arduino